Tuesday

May 26, 2015

May 26, 2015

Posted by **LISA** on Thursday, March 1, 2012 at 12:14am.

Find y' by implicit differentiation. Match the expressions defining y implicitly with the letters labeling the expressions for y'.

1. 7xsiny+2cos2y=2cosy

2. 7xcosy+2sin2y=2siny

a. 7cosy/7xsiny-4cos2y+2cosy

b. -(7siny/7xcos-4cos2y+2siny)

c. 7siny/4sin2y-xcosy-2siny

d. 7cosy/7xsiny+4sin2y+2cosy

- Calculus. I need help! -
**Steve**, Thursday, March 1, 2012 at 11:48am1.

7xsiny+2cos2y=2cosy

7siny + 7xcosy*y' - 4sin2y*y' = -2siny*y'

y' = 7siny/(-7xcosy + 4sin2y - 2siny)

is there a typo in (b) or (c)?

2.

7xcosy+2sin2y=2siny

7cosy - 7xsiny*y' + 4cos2y*y' = 2cosy y'

y' = 7cosy/(2cosy + 7xsiny - 4cos2y)

= (a)